PERBANDINGAN JUMLAH DATA DAN WAKTU LOADING ANTARA WEB TRADISIONAL DAN WEB BERBASIS AJAX - Radityo Adi Nugroho (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2011)
Until the beginning of 2005, the characteristic of the web application interaction always depends on the events given by the user. Moreover, must wait for the occurrance of the whole web page to move from one event to another. To repair this problems, appears the Asynchronous Javascript and XML(AJAX) technique which makes the web application similar to desktop application and not depends too much on the event given by the user. Ajax also be claimed has the shorter loading time. However, Ajax also has some weakness because its source code is hard to be written. Some frameworks appear to overcome this weakness, one of them is ASP.NET Ajax.This research tries to make an Ajax web application with ASP.NET Ajax to compare with the traditional web. The compared aspects in this research are the loading time and the data amount. The web application that made is tourism information in Daerah Istimewa Yogyakarta province.The result shows that the traditional web application has the shorter loading time in a whole page refreshing because it passes less data amount rather than Ajax web application using Atlas. However, to change a web page contents, Ajax web application using the ASP.NET Ajax has the shorter loading time because it passes less data amount.